METODE BERCERITA SEBAGAI ALAT PENDIDIKAN DI KB PELITA HATI - YUSNITA, YUSNITA; KENCANA, RITA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Early childhood education is a foundational stage of education that plays a strategic role in human resource development. Early childhood is considered a crucial and significant period in the educational process, as it has a major impact on subsequent learning stages. At this stage, children are in an optimal condition to develop various abilities, including physical, cognitive, language, socio-emotional, and spiritual aspects. Storytelling is one of the approaches used in early childhood education. The implementation of this method plays an important role in developing children's language skills. Through storytelling, children can be trained to express their thoughts or opinions and develop skills in continuing a story or fairy tale presented by the teacher. Therefore, teachers need to understand the role and function of storytelling in supporting children's language development optimally. This research focuses on the use of storytelling as an educational tool at KB Pelita Hati, involving the stages of planning, implementation, and evaluation. Teachers apply storytelling methods by encouraging children to engage in meaningful learning. One way to do this is by asking them to retell the knowledge they have acquired, whether from the school environment or real-life experiences. This approach aims to make children more active in the learning process, making learning activities more enjoyable and beneficial for their development. This study is a descriptive research with a quantitative approach, conducted at KB Pelita Hati. The subjects of this study were 14 students from KB Pelita Hati. The data were then analyzed using the formula P = ????/???? × 100% to determine whether the storytelling method as a learning tool for children reached 81.42%, categorized as